Peningkatan Persepsi Mahasiswa Terhadap Radikalisme di Era Globalisasi Melalui Mata Kuliah Pendidikan Pancasila - Rahayu, Ninik Sri; Khusna, Asmaul (Jurnal Pendidikan Kewarganegaraan, 2018)
The problem of radicalism in this globalization era is especially religious radicalism. The students learn the Pancasila Education course in Ideology Pancasila topic, students are expected to be able to understand radicalism so that it can counteract the radicalism circulating in the campus. The purpose of the Pancasila Education course in higher education, especially the subject of Pancasila as a State Ideology that is developing the Pancasila character. They are actualized in an honest, responsible, polite, friendly with their environment, mutual cooperation, and peace-loving attitude. In this research, tests were carried out on students' perceptions of radicalism. It was done before and after learning the Pancasila Education course. Measurement of student perceptions uses a Likert scale questionnaire with fifteen items. The questionnaire is divided into three aspects, namely the definition of radicalism, the purpose of radicalism, due to radicalism. Moreover, the questionnaire is classified into students who have very good, good, and sufficient understanding. From the two tests, it has resulted that there was an influence of Pancasila Education on students' perceptions of radicalism. After the Pancasila Education course, the perception of students in the same category gets an increase in total value.